Perception of Training and Specialization of Scientific Journalism in Chile [Percepción de la Formación y la Especialización del Periodismo Científico en Chile] - Vernal-Vilicic, T (Pontificia Universidad Catolica de Chile, 2019)
This article analyses the perception that journalists and science communication professors have about the training and specialization of Chilean scientific journalists, using a mixed methodology, consistingofin-depthinterviewsandnational surveys. Amongthemostoutstandingresults is that, although the pre-graduate and postgraduate training offer has increased inthecountry, thespecializationinscientific communicationinChilecontinuestodepend on self-training and labor specialization. Also, therearedifferentlevelsofappreciation of this among professionals. It is concluded that this assessment responds to work trajectories, training and informational models. © 2019 Pontificia Universidad Catolica de Chile. All rights reserved.